2021
DOI: 10.1088/1361-6560/ac16c1
|View full text |Cite
|
Sign up to set email alerts
|

Geometry calibration and image reconstruction for carbon-nanotube-based multisource and multidetector CT

Abstract: Conventional intraoperative computed tomography (CT) has a long scan time, degrading the image quality. Its large size limits the position of a surgeon during surgery. Therefore, this study proposes a CT system comprising of eight carbon-nanotube (CNT)-based x-ray sources and 16 detector modules to solve these limitations. Gantry only requires 45° of rotation to acquire the whole projection, reducing the scan time to 1/8 compared to the full rotation. Moreover, the volume and scan time of the system can be sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…[48][49][50] Besides, CNTs have the characteristics of electric field response, [51,52] and the development of combined treatment with IRE is significant. [53,54] According to the research results of Mao et al [55] CNTs have unique tumor targeting and local electric field amplification ability. Thereby, CNTs were combined with low-intensity nanosecond electric pulses (nsEPs).…”
Section: Cntsmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50] Besides, CNTs have the characteristics of electric field response, [51,52] and the development of combined treatment with IRE is significant. [53,54] According to the research results of Mao et al [55] CNTs have unique tumor targeting and local electric field amplification ability. Thereby, CNTs were combined with low-intensity nanosecond electric pulses (nsEPs).…”
Section: Cntsmentioning
confidence: 99%
“…In other research directions, some scholars have fabricated CNTs into targeted molecular probes for tumor diagnosis, combined with -X-ray, Computed tomography (CT), Magnetic Resonance Imaging (MRI), Positron Emission Computed Tomography (PET-CT), and other imaging equipment for targeted ablation and -post-treatment evaluation of tumors. [54,[64][65][66][67] Saghatchi F et al [68] have made preliminary exploration in this direction and made some achievements. Their previous research found that MWCNTs functionalized with magnetic Fe 3 O 4 and gold nanoparticles (AU-NPs) can act as contrast agents in CT scanning and ultrasonic imaging.…”
Section: Cntsmentioning
confidence: 99%
“…As a brief review of the literature, there is a wealth of calibration methods for cone-beam computed tomography (CT) and tomosynthesis imaging in diverse applications [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. They can broadly be separated into offline phantom-based calibration methods and online phantom-less methods [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid CT system has a unique architecture and presents a unique geometric calibration problem, with a unique set of information that can be used for calibration. Previously, a number of calibration methods have been developed for cone-beam tomosynthesis as well as computed tomography to meet the demand of diverse applications [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. They have been generally classified into offline phantom-based calibration methods and online phantom-less methods [ 28 ].…”
Section: Introductionmentioning
confidence: 99%